2013
DOI: 10.1068/i0580ic
|View full text |Cite
|
Sign up to set email alerts
|

Weak Priors versus Overfitting of Predictions in Autism: Reply to Pellicano and Burr (TICS, 2012)

Abstract: Pellicano and Burr (2012) argue that a Bayesian framework can help us understand the perceptual peculiarities in autism. We agree, but we think that their assumption of uniformly flat or equivocal priors in autism is not empirically supported. Moreover, we argue that any full account has to take into consideration not only the nature of priors in autism, but also how these priors are constructed or learned. We argue that predictive coding provides a more constrained framework that very naturally explains how p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 12 publications
3
63
1
Order By: Relevance
“…We suggested that this process may be atypical in autism, in that the internal priors are underweighted and less used than in typical individuals. Our theory has been followed by several others along similar lines (8)(9)(10)(11).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…We suggested that this process may be atypical in autism, in that the internal priors are underweighted and less used than in typical individuals. Our theory has been followed by several others along similar lines (8)(9)(10)(11).…”
mentioning
confidence: 71%
“…These mechanisms may be more readily explained by the recent Bayesian models of autism (4,(8)(9)(10)(11), which clearly predict that individuals with autism should give less weighting to prior or predictive information, such as the consequences of previous stimulation. Critically, in this study, number perception of autistic children postadaptation was more accurate, in that the target patch of dots corresponded better to physical reality than to expectations.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in Section 2.2, this relates to the idea that the perceptual system makes predictions or hypotheses about the nature of upcoming stimuli, which then become matched with incoming sensory information (Friston, 2005(Friston, , 2008. It has been argued that in autism these prior predictions may be less precise (Pellicano & Burr, 2012) or deployed in an inflexible manner possibly even resulting in hyper-precision Van de Cruys et al, 2013), meaning overall that perception becomes more sensitive to incoming stimuli but can be less influenced by context. This lack of top-down prediction in ASD has been suggested to underlie problems during the perception of visually ambiguous stimuli like illusory figures and could even extend to social stimuli such as facial expressions and biological movement .…”
Section: Deficient Predictive Codingmentioning
confidence: 99%
“…An optimal balance in SNR including top-down regulation in form of selection and filtering allows for optimal predictive coding of the environment (see also Pellicano & Burr, 2012;Van de Cruys et al, 2013). With intact top-down regulation (filtering, selection, integration) local encoding can be predictive for "what" should happen and "when" (Arnal & Giraud, 2012), thus mainly processing deviations from expectations, resulting in a system that is highly efficient and proactive to respond (see Fig.…”
Section: Core Features Of the Proposed Frameworkmentioning
confidence: 99%
“…In many of the recent proposals for ASD, deficient precision estimation is assumed to be key (Lawson et al, 2014;Palmer, Paton, Kirkovski, Enticott, & Hohwy, 2015;Pellicano & Burr, 2012;Van de Cruys, de-Wit, Evers, Boets, & Wagemans, 2013;Van de Cruys et al, 2014). Our own account, termed ''HIPPEA" (for High, Inflexible Precision of Prediction Errors in Autism), assumes that bottomup prediction errors are assigned a precision that is too high and not adapted (inflexible) to the uncertainty in the context (Van de Cruys et al, 2014).…”
Section: Introductionmentioning
confidence: 99%